Community Structure of Dung Beetles (Scarabaeidae: Scarabaeinae) in The Atlantic Forest of the Reserva Natural Vale (Linhares, Espírito Santo, Brazil) - C. Lima, Renan (2022)
There are 7000 species of Scarabaeinae beetles that can be divided into four functional guilds. The aim of this work was to describe the Scarabaeinae community, its functional guilds and fluctuation throughout the year at two sites in the Reserva Natural Vale, municipality of Linhares, Espírito Santo state, Brazil. The samples were carried out monthly, from June 2012 to January 2013, with pitfall traps exposed for 48 hours with human faeces and rotten pig baits. Comparisons between the areas were made through abundance analysis and species richness, besides relating the feeding guilds and nesting of the captured species. A total of 9039 specimens were collected, distributed in 16 genera and 34 species. The most abundant species were Dichotomius (Selenocopris) irinus (Harold, 1867) with 34.5%, Aphengium cupreum Shipp, 1897 with 24.5% and Canthon (Peltecanthon) staigi (Pereira, 1953) with 21.3%. Nine species were recorded in all samples, with 88% of the total species captured during the study. Two out of three most abundant species, D. irinus and A. cupreum were dominant in the dry season. C. staigi was the most abundant in rainy season. Human feces trap was the most effective. In relation to trophic guild, most species were considered specialist. Regarding nesting behavior, the majority are paracoprids, standard pattern of Neotropical region